Factors Affecting Adoption of E-Marketing Among Small and Medium Enterprise Food Manufacturers in Malaysia - Zainal Rashid, Muhammad Faizal (2011)
In Malaysia, one of the main sectors that can benefit substantially from the usage of E-Marketing is the agri food SMEs. On the other hand, the increasing importance of the presence of E-Marketing posed challenges to agri food SMEs owners, who have long depended on traditional and conventional marketing media. This is due to the fact that there are a lot of predictions and uncertainties on the potential of conducting E-Marketing over the Internet and confusion concerning exactly what is happening, how much potential exists, and what agri food SMEs should be doing to take the advantage of it is still debatable issues. The study generally aims to explore the factors affecting the adoption of E-Marketing among agri food SMEs in Malaysia. An online survey was posted at http://www.my3q.com. The survey focused only on agri food SMEs who have adopted E-Marketing in their firm. The invitation to participate in the questionnaire was sent via e-mail. A total of 239 participants responded to the online questionnaire. The data were analyzed using descriptive statistics, chi-square analysis, factor analysis, and logistic regression. Based on the results of the study, majority of the respondents are middle managers working in small enterprises located in the central region of Malaysia selling snacks, ready to serve foods, frozen foods, drinks and condiments. Most of the SMEs are fairly experience users of E-Marketing and believe that they will continue to use E-Marketing in the future. Internet Marketing, E-Mail Marketing, and Mobile Marketing are the preferred tools used when conducting their E-Marketing activities. In terms of the SMEs perceptions on the motivational context (technology, organization, and environment) factors for E-Marketing adoption in their firms, all of the contexts have a mean ranging from agree and neutral. Chi-square analysis reveals that only annual sales have a significant impact on E-Marketing level adoption. From the factor analysis, 3 factors have emerged from the technological context namely marketing function benefits, customer related benefits, and product related benefits. For the organizational context, 4 factors are extracted from the factor analysis namely compatibility, resources capabilities, firm size and changes in product types. Lastly, on the environmental context, 3 factors are produced from the factor analysis namely trust, competitive pressure, and government policy. In order to investigate the likelihood of E-Marketing continual usage in agri food SMEs, by using the factor scores of the factors extracted from the factor analysis as the independents variables, a logistic regression was conducted. Based on the findings, seven factors were found to be significantly related to the dependent variable (continue usage or otherwise) namely marketing function benefits, customer related benefits, product related benefits, compatibility, changes in product types, trust, and government policy. Therefore, the findings from this study could provide an important insight towards improving the E-Marketing sustainability in agri food SMEs in Malaysia. By identifying the possible factors for E-Marketing continual usage, organizations which would like to ensure the sustainability of E-Marketing in their firm will be able to apply strategies and make managerial decisions based on the findings from this research